Clinical effectiveness of paliperidone palmitate 3‐monthly and 1‐monthly as monotherapy in patients with schizophrenia: A retrospective cohort study based on the Medicaid claims database - Chih‐Lin Chiang; Madoka Chinen; Mehmet Daskiran; Akihide Wakamatsu; Ibrahim Turkoz (Wiley, 2024)
Abstract Aim Real‐world data (RWD) for paliperidone palmitate (PP) three‐monthly (PP3M) is lacking based on Japan label requirements. This study evaluated the clinical effectiveness of PP3M versus PP once‐monthly (PP1M) in patients with schizophrenia administered according to Japan label requirements. Methods Retrospective analyses were conducted using RWD from Merative™ MarketScan® Multi‐State Medicaid (MDCD) claims database (June 2015-December 2022). Adult patients with schizophrenia switching from PP1M to PP3M were included. Patients transitioning to PP3M were matched with patients who continued with PP1M using propensity score matching (PSM) at 1:1 ratio. Primary hypothesis aimed to investigate non‐inferiority of PP3M versus PP1M in terms of relapse‐free status at 24 months from index PP injection. Outcome measures were proportions of relapse‐free patients at 24 months, time to relapse, treatment persistence, and adherence. Results Total 4252 eligible adult schizophrenia patients on PP (PP3M:582; PP1M:3670) were identified. After PSM, each PP cohort comprised 562 matched individuals. Estimated proportion of relapse‐free patients was higher in PP3M (85.7%) versus PP1M (77.9%), per Japan PP label. PP3M demonstrated superiority to PP1M after testing for non‐inferiority in terms of achieving relapse‐free status at 24 months, with an estimated difference of 7.8% (95% CI: 1.7%-13.9%). PP3M cohort had lower risk of relapse (HR: 0.605; CI: 0.427-0.856), longer treatment persistence, and higher treatment adherence versus PP1M cohort. Conclusions Findings suggests that patients who switched to PP3M might be able to reduce risk of relapse compared to those who continued PP1M after aligning particularly with Japan's label requirements.